Distinct contributions of partial and full EMT to breast cancer malignancy - Lüönd, Fabiana; Sugiyama, Nami; Bill, Ruben; Bornes, Laura; Hager, Carolina; Tang, Fengyuan; Santacroce, Natascha; Beisel, Christian; Ivanek, Robert; Bürglin, Thomas; Tiede, Stefanie; van Rheenen, Jacco; et al. (Developmental cell, 2021)
Epithelial-mesenchymal transition (EMT) is a transient, reversible process of cell de-differentiation where cancer cells transit between various stages of an EMT continuum, including epithelial, partial EMT, and mesenchymal cell states. We have employed Tamoxifen-inducible dual recombinase lineage tracing systems combined with live imaging and 5-cell RNA sequencing to track cancer cells undergoing partial or full EMT in the MMTV-PyMT mouse model of metastatic breast cancer. In primary tumors, cancer cells infrequently undergo EMT and mostly transition between epithelial and partial EMT states but rarely reach full EMT. Cells undergoing partial EMT contribute to lung metastasis and chemoresistance, whereas full EMT cells mostly retain a mesenchymal phenotype and fail to colonize the lungs. However, full EMT cancer cells are enriched in recurrent tumors upon chemotherapy. Hence, cancer cells in various stages of the EMT continuum differentially contribute to hallmarks of breast cancer malignancy, such as tumor invasion, metastasis, and chemoresistance. [Display omitted] •Lineage tracing of partial and full EMT cells in breast cancer metastasis•Partial EMT cells cycle between hybrid EMT and epithelial stages•Partial, but not full, EMT cells are required for metastasis formation•Both partial and full EMT cells contribute to chemoresistance Lüönd et al. establish genetic lineage tracing systems to monitor mammary tumor cells undergoing early partial and late full epithelial-mesenchymal transition (EMT). They demonstrate that partial EMT cells, but not full EMT cells, are required for lung metastasis, while both contribute to the development of chemoresistance.